A new sensitivity model with blank space for layout optimization*Project supported in part by the National Natural Science Foundation of China (No. 61173088), the Science & Technology Program of Xi'an, China (No. CX1248 ⑤), and the 111 Project (No. B08038). (June 2017) - Wang, Junping; Wu, Yao; Liu, Shigang; Xing, Runsen
Abstract: As the technology scales advancing into the nanometer region, the concept of yield has become an increasingly important design metric. To reduce the yield loss caused by local defects, layout optimization can play a critical role. In this paper, we propose a new open sensitivity-based model with consideration of the blank space around the net, and study the corresponding net optimization. The proposed new model not only has a high practicability in the selection of nets to be optimized but also solves the issue of the increase in short critical area brought during the open optimization, which means to reduce the open critical area with no new short critical area produced, and thereby this model can ensure the decrease of total critical area and finally achieves an integrative optimization. Compared with the models available, the experimental results show that our sensitivity model not only consumes less time with concise algorithm but also can deal with irregular layout, which is out of the scope of other models. At the end of this paper, the effectiveness of the new model is verified by the experiment on the randomly selected five metal layers from the synthesized OpenSparc circuit layout.